Biochar modulates the antioxidant system and hormonal signaling in tobacco under continuous-cropping conditions - Yuan Ye; Zhou Qiuxue; Yao Tongtong; Cui Congcong; Wang Yue; Qiao Chan; Jiao Yusheng; Sun Hongwei; Huang Qinchao; E. Zhiying; Yin Kuide; Zhang Huihui (Journal of Plant Interactions)
As an important economic crop, tobacco faces the common challenges of continuous cropping due to the limited amount of arable land. Biochar has certain preventive and control effects on continuous cropping obstacles and can improve crop yield and quality. This study aims to explore the regulation of the antioxidant system and hormone signaling in tobacco under continuous cropping conditions by biochar. We studied the impact of biochar (Nicotiana tabacum LJ911 and LY101) on plant physiological functions and transcriptomes of tobacco under continuous cropping conditions. The results showed that biochar regulates photosynthetic gas exchange parameters in both tobacco varieties. Biochar significantly increased the activity of antioxidant enzymes in the leaves of both tobacco varieties under continuous-cropping conditions. Additionally, biochar up-regulated endogenous abscisic acid, auxin, and jasmonic acid in the leaves of both tobacco varieties, with higher levels observed in LY101 than in LJ911. Through Weighted Gene Co-expression Network Analysis (WGCNA), it was found that the tobacco antioxidant system and hormones showed a significant response. Biochar improved photosynthetic efficiency, enhanced antioxidant capacity, and promoted tobacco growth through hormone synthesis and signaling. In summary, biochar application can serve as a promising strategy to mitigate the challenges associated with continuous cropping in tobacco cultivation.